Alpinia zerumbet potentially elevates high-density lipoprotein cholesterol level in hamsters - Lin, Li-Yun; Peng, Chiung-Chi; Liang, Yu-Jing; Yeh, Wan-Ting; Wang, Hui-Er; Yu, Tung-Hsi; Peng, Robert Y (Journal of agricultural and food chemistry, 2008)
In folkloric plant medicines, Alpinia zerumbet (AZ) has been popularly recognized as an exellent hepatoprotector. To search for a good high-density lipoprotein cholesterol (HDL-C) elevating herbal preparation, we examined AZ for its antioxidant and hypolipidaemic bioactivities, especially its HDL-C elevating activity. AZ seeds contain 0.51% essential oils (SO), which are comprised of monoterpenoids, oxygenated monoterpenoids, sesquiterpenoids, oxygenated sesquiterpenoids, aldehydes, acid, and esters. Gas chromatography/mass spectrometry analysis indicated that most of the monoterpenes and sesquiterpenes were recoverable in pentane eluent, whilst the oxygenated monoterpenoids and sesquiterpenoids remained in ether eluent. The high contents of rutin, quercetin, and polyphenolics in ethanolic extract of AZ seeds exhibit moderate antilipoperoxidative but potent DPPH free radical scavenging bioactivities. Conclusively, both seed powder (SP) and SO are effective hypolipidaemics with amazingly potent HDL-C elevating capabilities. On the basis of hepatoprotectivity, SP is a more feasible hypolipidemic agent as well as a promising HDL-C elevating plant medicine.